A synthesis and appraisal of clinical practice guidelines, consensus statements and Cochrane systematic reviews for the management of focal spasticity in adults and children. Issue 4 (13th February 2022) - Williams, Gavin; Singer, Barby J.; Ashford, Stephen; Hoare, Brian; Hastings-Ison, Tandy; Fheodoroff, Klemens; Berwick, Steffen; Sutherland, Edwina; Hill, Bridget
Abstract: Objective: To identify and appraise the existing clinical practice guidelines, consensus statements and Cochrane systematic reviews for the management of adult and paediatric focal spasticity to generate a single synthesized guideline. Methods: Systematic review of 12 electronic databases. Clinical practice guidelines, consensus statements and Cochrane systematic reviews for focal spasticity in adults and children. Included studies were appraised according to the AGREE II criteria. Results: A total of 25 papers were included in this review, comprising 12 clinical practice guidelines, nine consensus statements and four Cochrane systematic reviews. The areas most strongly endorsed were: (1) management to be provided by a multi-disciplinary team, (2) therapy should be goal-directed, (3) goals to be developed in conjunction with the patient and family, and (4) importance of follow-up evaluations. There was a greater focus on activity outcomes and classification in the paediatric papers. The guidelines varied considerably in their quality, with AGREE II scores ranging from 52.8 to 97.1%. Conclusions: This systematic review has synthesized the key elements regarding principles of focal spasticity management, outcome measures, physical interventions and educational recommendations into a single, readily applied guideline available for clinical use. Despite considerable variability in the quality of the guidelines, several strong themes emerged. Implications for rehabilitation: Focal spasticity management should be multi-disciplinary, patient-centred and goal-directed. Routine measurement of impairment and activity are strongly endorsed. Botulinum toxin A injection should only be provided as part of an integrated approach to focal spasticity management.